(3ZGjI GdeQGe aj JGQjN eMGSf HZOGO OGQ GdSdGes - (3jGSjf Hf NjQGddg Hf eMehO Hf ehSi GdNWjH GdYeQj,J (B1232 (3g` s
(3ChdgG (B:s
(3hHYO eGRdJ eJhdYkG HLeY GdJhGQjN aCLHJ Gf CLeY JGQjNkG dHZOGO, EP gi OGQ GdeQGO s
(3BNQgG (B:s
(3hdGRGdJ jGHf GdCcQejf ebOekG Ydi cd Pi SHb hbO WG (B[(3ef(B] (3GdOgQ s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B129 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B177s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B781 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B300 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs